Wood and coals as witnesses of the paleo-environment, plant economy and ritual world of Pre-Columbian Peru. Methodology and problems - Moutarde, Fanny (2007)
Anthracology is the study of wood charcoals found in archaeological contexts or in natural stratigrafies. The taxonomical determination of the wood charcoals lets deal with issues like palaeo-environment and the use of wood as raw material, fuel or liturgical tool by the past societies. In spite of the high informative potential of wood charcoals and their abundance on the Peruvian archaeological sites, particularly the coastal ones, anthracology is not welldeveloped in Peru. As such, this article introduces the anthracological discipline, presenting, firstly, its historical background ; then defining what “wood” and “wood charcoals” refer to ; thirdly, explaining the methodology of sampling and study of anthracological material ; lastly, the problematics that could be tackled with an anthracological study would layed out.